Beam Data Validation during Transition from Flattened to Unflattened Beams in IMRT and VMAT Delivery: An Experimental Study - Pradeep Goswami; Punam Kumari; Brijesh Goswami; Rakesh Kumar Jain; Suresh Yadav; S Choudhary; Asiya Hilal; Kishore Singh (Journal of Clinical and Diagnostic Research, 2025)
Introduction: The commissioning process for Intensity-Modulated Radiotherapy (IMRT) and RapidArc is very rigorous and tedious. It involves manifold beam data measurement, Quality Assurance (QA) and acceptance testing of different parts of Linear Accelerator (Linac). Aim: To find out how the commissioning parameter of TG-119 will change when it is shifted from a flattened beam (6X) to Flattening Filter Free (6X_FFF) for RapidArc and IMRT plans. Materials and Methods: In this experimental study conducted at the Department of Radiation Oncology, Subharti Medical College, Meerut, Uttar Pradesh, India, between December 2021 to November 2022 the authors evaluated the effect of dose rate, gantry speed, leaf speed and intentional error by Picket Fence (PF) tests using Electronic Portal Imaging Device (EPID) and GafchromicTM EBT3 films during commissioning of TrueBeam Linac (Varian Medical System, Palo Alto, CA). For comparison, RA and IMRT plans are made for all tests as per American Association of Physicists in Medicine Task Group-119 (AAPM TG-119). Confidence Limit (CL) was set to have 95 percent of the measured data within tolerance limit. Results: For IMRT (static and arc mode) recommendations and methodology were evaluated effectively to check commissioning parameter precision. Average absolute deviation (DiffAbs) for variable Dose Rate and Gantry Speed (DR_GS) has been within 1.5 % for both 6X and 6X_FFF energies. Their (DiffAbs) for variable Leaf Speed and Dose Rate (LS_DR) was also within 1.5%. Result for field-by-field measurements for IMRT and RapidArc for 6X and 6X_FFF energies shows that overall mean for 6X energy is 99.83 and 99.88, respectively, for IMRT and RapidArc cases, with CL values of 0.50 and 0.32. The 6X_FFF energy result is 99.81 and 99.87 for IMRT and RapidArc cases, with CL values of 0.55 and 0.34.In comparison to RapidArc, IMRT plans have more Monitor Units (MUs). RapidArc plans require less time to deliver the same or better results than IMRT plans. Conclusion: Accurate delivery of RapidArc and IMRT plans for different beam modalities (6X and 6X_FFF), accepted CL values can be utilised as a baseline to evaluate the quality of QA procedure, accuracy and wholeness of Treatment Planning System (TPS).